The Influence of Blue Accounting, Corporate Social Responsibility, and Stakeholders Influence Capacity on Financial Performance - KHADDAFI, MUAMMAR; ., MUNANDAR; ., CHALIRAFI; ., NAZARUDDIN; ., MIRANDA; ILHAM, RICO NUR (Journal of Ecohumanism, 2024)
This study aims to determine the effect of green accounting, blue accounting, corporate social responsibility (CSR), and stakeholders influence capacity on financial performance. The sample in this study was the Maritime sector companies listed on the Indonesia Stock Exchange in 2021-2022. In drawing samples, the author used a purposive sampling technique, namely a sample selection method based on certain criteria. The data used were obtained from the Indonesia Stock Exchange publication and the official website of each company. This study used 24 samples with 2 years of observation so that the total was 48 observations with multiple linear regression estimation of panel data. The results showed that the green accounting variable was negative and insignificant on financial performance, blue accounting had a positive and insignificant effect on financial performance, corporate social responsibility had a positive and insignificant effect on financial performance, stakeholders influence capacity had a positive and significant effect on financial performance.